Perlindungan Hukum Perempuan Korban Pelecehan Seksual Dalam Sistem Peradilan Pidana Indonesia Ditinjau Dalam Prespektif Viktimologi - Dida Rachma Wandayanti (Pusat Studi Gender Universitas Jember, 2022)
The lack of literature and understanding of law enforcement agencies regarding victimology in Indonesia is an important question of how so far legal protection for women victims of sexual harassment in the criminal justice system. Several internal policies regarding how to handle women's cases in each agency have been made, but they need to be reviewed regarding their implementation of the rights of women victims of sexual harassment. Victimology as a comprehensive and in-depth study of victims needs to be the foundation of the Indonesian criminal justice system. In this study, we want to see to what extent victimology is used in the Indonesian criminal justice system in looking at the cases of women victims of sexual harassment. The research is a social legal research with a descriptive analytical approach. The results of the study indicate that sexual harassment as a type of sexual violence in Indonesia has not fully used victimology studies. For example, it has not been regulated through valid legal policies, law enforcement has not had a perspective on women, and the results of court decisions against victims of sexual harassment have not fully protected women's rights.